Interaction between age and fatigue on antagonist muscle coactivation during an acute post-fatigue recovery phase - Harper, Sara A.; Thompson, Brennan J. (Frontiers in Aging, 2022)
This study investigated the age-related changes in antagonist muscle coactivation of the biceps femoris (BF) during an acute recovery period following a leg extensor fatiguing protocol. Twenty-three young (mean ± SD: age = 25.1 ± 3.0 years) and twenty-three old men (age = 71.5 ± 3.9 years) participated. Surface electromyography (sEMG) was recorded from the BF muscles for antagonist muscle coactivation. Testing involved participants performing leg extension isometric maximal voluntary contractions (MVCs) and isokinetic MVCs at 240°·s−1 at baseline (Pre) and again after the fatigue protocol at 0 (Post0), 7 (Post7), 15 (Post15), and 30 (Post30) minutes post fatigue. Root mean square (RMS) values were computed from the BF sEMG and were calculated as the first 200 ms from onset for the isometric (IsomCoact200ms) and dynamic isokinetic 240°·s−1 (DynCoact200ms) MVCs, and for the final 10° of the leg extension (DynCoact10°) on the isokinetic 240°·s−1 MVCs. Two-way ANOVAs [age group (young vs. old) × time (Pre vs. Post0 vs. Post7 vs. Post15 vs. Post30)] showed that DynCoact200ms had an effect for time (p = 0.018), with greater antagonist coactivation in Pre than Post0 (p = 0.009) and recovering by Post7 (p = 0.011) with no group differences. DynCoact10° had no age × time interaction (p = 0.070), but had a main effect for time (p = 0.020) with the Post0 being lower than the Pre. However, for this variable the young group showed a more severe Pre to Post0 fatigue decline (−45.9%) than the old group (−6.7%) indicating this may be a more sensitive variable for capturing age-related antagonist coactivation post-fatigue responses. Leg extensor fatigue affects some BF coactivation sEMG variables more than others, and any altered post-fatigue coactivation response recovers rapidly (<7 min) from baseline levels.